Information Structure Projects in Syntax: Evidence from focus and Modality in Sinhala - Ananda, M.G.L. (My University, 2018)
The major claim of this paper is that information structure related particles of Sinhala are distinct functional heads and they project in syntax. This is in line with the cartographic approach to syntax which claims that discourse related features are visible for computation (Rizzi 1997, 2004), a claim also supported by Miyagawa, (2010), and Aboh (2010), among others. The present paper seeks to validate the above claim with evidence from Sinhala, motivating the argument that discourse related features lexicalized in Sinhala drive the derivation, and these features are comparable to formal features in establishing an Agree relation.
Keywords: information structure, functional heads, Sinhala, syntax